Reducing death anxiety by using positive patterns of facing death in Islamic teachings - Hosein Sharifi; Masood Azarbayejani; Mohammad Davoudi (اخلاق وحیانی)
The most common and underlying human anxiety is death anxiety, which sometimes turns into morbid anxiety and falls into the category of moral vices. In this study, based on religious teachings and positive examples of facing death, ethical strategies to reduce death anxiety, deal with it properly and go through this important stage of life are presented. In this research, using qualitative content analysis and qualitative method of religious knowledge ijtihad, we tried to achieve a coherent classification of verses and hadiths related to death and types of encountering it by following and examining Islamic teachings; Therefore, the types of positive moral encounters with death and the indicators of achieving it were inferred and extracted in order to increase awareness and strengthen insight with a cognitive approach and thus reduce anxiety and desirable exposure to death.Extracting positive examples of facing death such as death in believing in God, death in Islam, death in purity, death with a confident soul, martyrdom, death with knowledge and guardianship of the Ahlal-Bayt of the Prophet and death while studying science can be The title of the findings of this study. Introducing some moral indicators such as: strengthening worship programs, preparing for death with righteous and lasting deeds, forsaking sin, repentance, strengthening sincerity, increasing knowledge of God, creating and strengthening knowledge and communication with the infallibles can be considered as the results of the article.